Who Gardens and How in Urban USA: Informing Social Equity in Urban Agriculture Action Plans - Das, Kirti; Ramaswami, Anu (Frontiers in Sustainable Food Systems, 2022)
Urban agriculture is increasingly incorporated into food system policies to address social equity. However, assessing its effectiveness requires primary data on the demographics of agricultural gardeners and the type of gardening pursued, which are limited. This paper reports on a first detailed survey of 6,152 representative urbanites in three US cities, enabling a detailed demographic analysis of agricultural gardeners. We find low engagement in community versus household agricultural gardening (~2% vs. ~27%). Indoor and outdoor household agricultural gardening was generally dominated by higher-income, White, males (24–44%). Community agricultural gardening appears more diverse; however, participation is low, hence, benefits may not scale up. Designing urban agriculture to address social equity requires gathering data on who gardens and how, for which our paper provides a first template.